MENINGKATKAN PERILAKU HIDUP SEHAT TERHADAP MASYARAKAT DESA SUKARATU KECAMATAN MAJASARI DI MASA PANDEMI COVID-19 - Sri Ndaru Arthawati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
Patterns of healthy living behavior, namely all health rules that are applied with awareness from within oneself without coercion to take health action against himself, his family, or the surrounding environment. Prevention is better than cure is the foundation of health which forms the basis of a healthy life implementation program. During the Covid-19 pandemic, the people of Sukaratu Village, Majasari District must be able to implement health protocols with the aim of reducing the level of Covid-19 transmission and remaining productive in carrying out daily activities. The application of social distancing and physical distancing in order to assist the government's efforts in preventing and spreading Covid-19.